Aksiologi Filsafat Pendidikan Islam Sebagai Dasar Pembentukkan Manusia Paripurna (Insan Kamil) - Isval Maulana; Abdul Khobir (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Axiology is a branch of philosophy that examines values ​​in human life, such as goodness, truth, beauty, and the benefits of knowledge. In the context of Islamic education, axiology plays a crucial role in determining the direction and goals of education, namely, to develop individuals who are balanced intellectually, morally, and spiritually, known as insan kamil (the perfect human being). Values ​​in axiology are divided into two primary sources: divine values ​​derived from God's revelation and His attributes, and human values ​​derived from human experience and civilization. These two types of values ​​serve as the foundation for developing a comprehensive Islamic education. The axiology of Islamic education emphasizes not only the attainment of knowledge but also the formation of character and morals in students. Teachers and educational institutions act as agents of values, instilling ethics, aesthetics, and socio-political awareness based on Islamic teachings. By integrating these values, Islamic education aims to produce a generation that is not only intellectually intelligent but also possesses noble morals and is capable of making a positive contribution to society and global civilization. Axiology, therefore, serves as a crucial foundation for realizing a meaningful and humanity-oriented education.